FENOMENA PERUNDUNGAN DALAM NOVEL AYAH MENGAPA AKU BERBDEDA KARYA AGNES DAVONAR - Suryadi, Irfan; Hayati, Yenni; Nasution, Muhammad Ismail (Universitas Negeri Padang, 2018)
This study aimed to: (1) describe the form of abuse; (2) describe the causes of abuse; and (3) describe the impact of abuse in Ayah Mengapa Aku Berbeda novel by Agnes Davonar. Theories used to achieve the objectives of the research, namely: (1) the nature of the novel; (2) novel elements; (3) fiction analysis approach; (4) literature sociology studies; (5) abuse; (6) causes of abuse; and (7) the impact of abuse. This type of research is qualitative research using descriptive methods. The data in this study are sentences and direct speeches of the characters and narratives of the author that can be interpreted or interpreted as abuse. The source of the data in this study was Ayah Mengapa Aku Berbeda novel by Agnes Davonar. The research data collection technique was carried out with the following steps: (1) reading Ayah Mengapa Aku Berbeda novelby Agnes Davonar; (2) marking quotes in novels that correspond to the data sought; and (3) record data on abuse, causes of abuse, and the impact of abuse in Ayah Mengapa Aku Berbeda novelby Agnes Davonar. After the data is collected, the data are analyzed with the following steps: (1) identifying data; (2) clarifying or analyzing data; and (3) make conclusions. Based on the results of the study, it can be concluded that the indicators of abuse phenomenon contained in the novel Ayah Mengapa Aku Berbeda novel the work of Agnes Davonar include: (1) forms of abuse divided into three; verbal abuse, nonverbal abuse, and physical abuse; (2) the causes of abuse are divided into two; individual factors and social factors, and (3) the impact of abuse is divided into two; the impact on victims and the impact on the perpetratorsKeywords: Bullying, Novel, Social